Principles in the management of a mangled hand - K S Alphonsus Chong (Indian Journal of Plastic Surgery)
Mangling hand injuries are high energy complex conditions that are challenging to manage. They require careful planning and meticulous execution of treatment. A clear set of anatomical and functional goals at the outset guides the planning. The first surgery is crucial to ensure good vascularity to the salvaged tissue, prevent infection and achieve bony stabilization. Re-look surgery and definitive reconstruction can then follow. Post-operative therapy is an important component of treatment. Despite best efforts, outcomes are variable in these devastating injuries. Secondary procedures and provision of prostheses will do much to improve the patient′s body image and limb function. This article provides a set of principles that will guide the assessment and treatment of such injuries.